Modulations in the Peripheral Immune System of Glioblastoma Patient Is Connected to Therapy and Tumor Progression—A Case Report from the IMMO-GLIO-01 Trial - Rühle, Paul F.; Goerig, Nicole; Wunderlich, Roland; Fietkau, Rainer; Gaipl, Udo S.; Strnad, Annedore; Frey, Benjamin (Frontiers in Neurology, 2017)
Immune responses are important for efficient tumor elimination, also in immune privileged organs such as the brain. Fostering anti-tumor immunity has therefore become an important challenge in cancer therapy. This cannot only be achieved by immunotherapies as already standard treatments such as radiotherapy and chemotherapy modify the immune system. Consequently, the understanding of how the tumor, the tumor microenvironment, and immune system are modulated by cancer therapy is required for prognosis, prediction and therapy adaption. The prospective, explorative and observational IMMO-GLIO-01 trial was initiated to examine the detailed immune status and its modulation of about 50 patients suffering from primary glioblastoma multiforme (GBM) or anaplastic astrocytoma during standard therapy. Prior to the study, a flow cytometry-based assay was established allowing the analysis of 34 immune cell subsets and their activation state. Here, we present the case of the first and longest accompanied patient, a 53-year old woman suffering from GBM in the front left lobe. In context of tumor progression and therapy, we describe the modulation of the peripheral immune status over 17 months. Distinct immune modulations that were connected to therapy response or tumor progression were identified. Inter alia, a shift of CD4:CD8 ratio was observed that correlated with tumor progression. Twice we observed a unique composition of peripheral immune cells that correlated with tumor progression. Thus, following up these immune modulations in a closely-meshed manner is of high prognostic and predictive relevance for supporting personalized therapy and increasing therapy success. Trial registration: ClinicalTrials.gov NCT02022384 (registered retrospectively on 13th of December, 2013).